The presumption of gult created by Section 235(2) of the Tax Administration Act: a constitutional and comparative perspective - Faifi, Farai (Rhodes University, Faculty of Commerce, Department of Accounting, 2014)
This research examined the legal nature of the presumption of guilt created by section 235(2) of the South African Tax Admiration Act and considered whether or not its practical application violates the taxpayer's fundamental right contained in section 35(3) of the Constitution, which gives every accused taxpayer the right to a fair trial, including the right to be presumed innocent. The research also provided clarity on the constitutionality of this presumption because it has been widely criticised for unjustifiably violating the taxpayer's constitutional right to a fair trial. The conclusion reached is that the presumption created by section 235(2) of the Tax Administration Act constitutes an evidentiary burden rather than a reverse onus. It does not create the possibility of conviction, unlike a reverse onus where conviction is possible, despite the existence of a reasonable doubt. Therefore, it does not violate the accused taxpayer's the right to a fair trial and the right to be presumed innocent and hence it is constitutional. Accordingly, the chances that the accused taxpayer will succeed in challenging the constitutionality of section 235(2) of the Act are slim.
Keywords: Guilt (Law) -- South Africa; Presumption of innocence -- South Africa; Income tax -- Law and legislation -- South Africa; Human rights -- Taxation -- South Africa; Taxpayer compliance -- Moral and ethical aspects -- South Africa; Taxation -- South Africa